Michel Houellebecq: Google, Plagiarism, and Postproduction. - Williams, Russell (Contemporary French & Francophone Studies, 2019)
This article explores the notorious contemporary French writer Michel Houellebecq in a way that differs from the major critical approaches to his work. While there is a tendency to investigate, describe, and (perhaps) celebrate his individual style, this essay questions the extent to which he is a product of the Google era, and how this manifests in the formal dimension of his work. In doing so, this essay suggests a new way of reading this provocative writer, one that has implications for the contemporary reading, writing, and teaching of literature in the Academy.